2016
DOI: 10.32674/jis.v6i3.348
|View full text |Cite
|
Sign up to set email alerts
|

International Students and Mental Health

Abstract: Since the early 2000s, reports of increased rates of mental ill health among young people worldwide have received much attention. Several studies indicate a greater incidence of mental health problems among tertiary students, compared with the general population, and higher levels of anxiety, in particular, among international students compared with domestic students. Australia is host to many thousands of international students of an age when mental illnesses are most likely to surface. However, this issue ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 0 publications
3
60
1
2
Order By: Relevance
“…Nonspecific to the environment created by the pandemic, participants raised factors such as highly independent learning environments, a shortage of formal opportunities outside the classroom for social interaction with others, lacking a sense of belonging and racism as key challenges they have faced whilst studying in Australia. These factors were then also cited as a major cause of participants stressors and worries, a finding consistent with the associations shown in Study 1 as well as previous research (Forbes-Mewett & Sawyer, 2016;Sawir et al, 2008).…”
Section: Brief Discussion To Studysupporting
confidence: 87%
See 3 more Smart Citations
“…Nonspecific to the environment created by the pandemic, participants raised factors such as highly independent learning environments, a shortage of formal opportunities outside the classroom for social interaction with others, lacking a sense of belonging and racism as key challenges they have faced whilst studying in Australia. These factors were then also cited as a major cause of participants stressors and worries, a finding consistent with the associations shown in Study 1 as well as previous research (Forbes-Mewett & Sawyer, 2016;Sawir et al, 2008).…”
Section: Brief Discussion To Studysupporting
confidence: 87%
“…compounded by new and unfamiliar social and academic environments (Weier & Lee, 2016). For international students, mental health concerns have been found to be greater in both occurrence and severity compared to domestic students (Forbes-Mewett & Sawyer, 2016;Forbes-Mewett, 2019). Indeed, within the breadth of challenges faced by international students when relocating to study in a foreign country, mental health issues are among the most prevalent threats to international students' health.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Research has found that international students encounter difficulties with language barriers, finances, adjustments to a new educational system, social customs and norms, and homesickness (Gold, 2016;Ma, 2020;Mukminin, 2019;Tang et al, 2018;Telbis et al, 2014;Xing & Bolden, 2019). These challenges can impact their mental well-being (Forbes-Mewett & Sawyer, 2016;Koo, Kim, et al, 2021). Researchers estimate that 15%-20% of international students are at risk of experiencing mental health problems due to acculturative stress and acculturation-related problems (Zhang & Goodson, 2011).…”
Section: Introductionmentioning
confidence: 99%